Sistem Kontrol Portable Fuel Transfers Pump Berbasis Android Untuk Efektifitas Pengisian BBM Helikopter Penerbad - Wahyu Imam Fauzi; Mokhammad Syafaat; Dekky Widiatmoko (Universitas Darul Ulum, 2023)
The Army Aviation Operations Task is carried out in remote areas that still have minimal airport services, the process related to refueling for aviation helicopters is an obstacle to the implementation of the main tasks of aviation. So a tool is needed to make the process more effective. In this study, a method is used to obtain data for quantitative research to prove the hypothesis. The method is known as the Development Life Cycle Waterfall Diagram and experimental research. Currently still using a hand pump, therefore a portable tool is needed and uses an electric pump. specifically for fuel controlled by Arduino and an Android application as an input for a filling command and can store filling data. In this case, the tool system uses supporting components, namely batteries, Bluetooth hc 05, 5v relays, and flow sensors. With the research of portable pump tools, the process can be more efficient than hand pumps. When refueling a helicopter, simply by inputting the filling value from the Android application, the filling is running and the filling data is stored in the Android file.